Comparison of the effect of the mat and reformer pilates exercises on the waist-hips ratio and body compositions of the middle-aged sedentary women - Bastık, Canan; Cicioğlu, Halil İbrahim (Progress in Nutrition, 2020)
Study Objectives: The aim of this study was to compare the effects of the 8-week mat and reformer pilates exercises on body composition and waist-hip ratios of middle-aged sedentary women. Methods: Fifty-eight volunteer women participated in the study. Body compositions of women were measured by bioelectrical impedance analyzer, and waist and hip circumference were measured a using tape measure. In the analysis of the obtained data, two-way repeated-measures ANOVA was used. In addition, Bonferroni post-hoc test was used to determine the source of the difference between the groups. In addition, the changes in waist-hip ratios and body compositions of adult women for eight-week exercises were determined using the formula %Δ = [(Post-test - Pre-test) / Pre-test * 100]. Results: Body mass index, body fat mass, fat-free mass, and waist-hip ratios of the exercise groups were found to be statistically different from the control group (p